Quercetin alleviates acute kidney injury by inhibiting ferroptosis - Wang, Yue; Quan, Fei; Cao, Qiuhua; Lin, Yanting; Yue, Chongxiu; Bi, Ran; Cui, Xinmeng; Yang, Hongbao; Yang, Yong; Birnbaumer, Lutz; Li, Xianjing; Gao, Xinghua (Journal of advanced research, 2021)
A proposed model illustrating the therapeutic effect of QCT on AKI. QCT inhibits the expression of ATF3. While ATF3 blocks the system Xc-, and then suppresses GPX4, inducing ferroptosis. In another side, ferroptotic cells secrete chemokines like CCL2, CCL7, induce the recruitment of macrophages, and then cause the inflammation in AKI. In summary, QCT ameliorates AKI through the inhibition on ferroptosis and the following inflammation. [Display omitted] •Quercetin (QCT) inhibits ferroptosis but not apoptosis, necrosis or autophagy of renal proximal tubular epithelial cells, and ameliorates AKI induced by ischemia–reperfusion (I/R) or folic acid (FA).•Activation transcription factor 3 (ATF3) plays an important role in cell ferroptosis, while QCT significantly inhibits the expression of ATF3 and further blocks the downstream signaling pathway of ferroptosis.•Ferroptotic cells induce the recruitment and chemotaxis of macrophages through CCL2, triggering inflammation and enhancing tissue injury. Ferroptosis is an iron-dependent regulated necrosis and has been proven to contribute to the progress of acute kidney injury (AKI). Quercetin (QCT), a natural flavonoid which is commonly found in numerous fruits and vegetables, has extensive pharmacological effects, such as anti-oxidant, anti-inflammatory and anti-senescence effects. This study aims to explain whether ferroptosis is a therapeutic strategy to AKI, and to explore the effect of QCT on AKI ferroptosis. NRK-52E cells and HK-2 cells were used for in vitro ferroptosis studies. Morphology of cells was detected by transmission electron microscopy. Lipid ROS was assayed using flow cytometry. In vivo, AKI was induced by ischemia–reperfusion (I/R) or folic acid (FA). To explore the molecular mechanisms, RNA-sequence analysis was performed. Transwell was used to detect macrophage migration. We discovered that quercetin (QCT), a natural flavonoid, inhibited ferroptosis in renal proximal tubular epithelial cells. QCT blocked the typical morphologic changes of ferroptotic cells by reducing the levels of malondialdehyde (MDA) and lipid ROS and increasing the levels of glutathione (GSH). Moreover, QCT ameliorated AKI induced by I/R or FA. RNA-sequence analysis highlighted activation transcription factor 3 (ATF3), as it was the dominant one among all the 299 down-regulated genes by QCT. Knockdown of ATF3 could significantly increase the levels of SLC7A11, GPX4 and increased the cell viability. In addition, ferroptotic cells were found to be extremely pro-inflammatory by recruiting macrophages through CCL2, while QCT inhibited the chemotaxis of macrophages induced by ferroptosis in AKI. Collectively, these results identify QCT as a ferroptosis inhibitor and provide new therapeutic strategies for diseases related to ferroptosis.